Effects of GTAW Dynamic Wire Feeding Frequencies on Fatigue Strength of ASTM A516-70 Steel Welded Joints - das Neves, Nasareno [UNESP]; Fernandes, Martin Ferreira [UNESP]; Von Dollinger, Christian Frederico de Avila; Assis, João Marcos Kruszynski; Voorwald, Herman Jacobus Cornelis [UNESP] (Springer Nature, 2022)
It is known that the conventional arc welding processes reduce the fatigue life of welded joints. However, in this work, a gas tungsten arc welding process with dynamic wire feeding (GTAW-DWF) at frequencies of 0.5, 5, 10 and 15 Hz improved the fatigue properties compared to the conventional process (C-GTAW) and the unwelded base material. The investigation was based on axial fatigue tests (R = 0.1) at room temperature, microhardness tests, microstructural analysis, secondary dendritic arm spacing (SDAS) measurements, scanning electron microscopy of fatigue fracture surfaces and Weibull distribution analysis. The mechanisms associated to dendritic morphology of fusion welds and solidification patterns were discussed. The SDAS values were (5 ± 0.8), (4 ± 1.0), (2 ± 0.3) and (4 ± 0.7) µm for the GTAW-DWF process with frequencies of 0.5, 5, 10 and 15 Hz, respectively, compared to (6 ± 1.4) µm of the conventional process. The GTAW-DWF lower SDAS and the absence of micro solidification defects were associated with the fatigue life improvement. The fatigue life for the GTAW-DWF with 1 Hz welded joints improved the fatigue life from 3288 to 115,356 cycles and from 12,027 to 522,143 cycles for maximum stress levels of 534 and 481 MPa, respectively, compared to the conventional GTAW process.
Keywords: ASTM A516-70 steel; dynamic wire feeding; fatigue life; GTAW; welded joints; welding